Implementasi Program Disiplin Positif Dalam Membentuk Karakter MAJU (Mandiri, Agamis, Jujur, Unggul) Siswa Kelas VIII di SMPN 15 Bandung - Muftia Salma Nurpadilah; Ikin Asikin; Dinar Nur Inten (UNISBA Press, 2024)
Abstract. The use of punishment is often used by schools as a form of disciplining their students. Even though to discipline children do not always have to use punishment, through an agreement made between two parties can train discipline and responsibility for children. Research methods are carried out using qualitative methods. The purpose of this study is to provide insight into planning, processes, evaluations and outcomes, as well as inhibiting and supporting factors of positive discipline programs. The data collection used are interviews, observations, and documentation studies. Data analysis consisting of data reduction, data display, and conclusions. The results showed that (a) Planning a positive discipline program at SMPN 15 Bandung in shaping the character of MAJU (Independent, Religious, Honest, Superior). (b) The process of implementing a positive discipline program in shaping the character of MAJU (Independent, Religious, Honest, Superior). (c) The evaluation and results of the implementation of positive discipline in shaping the character of MAJU (Independent, Religious, Honest, Superior). (d) The inhibiting and supporting factor of the implementation of positive discipline at SMPN 15 Bandung in shaping the character of MAJU (Independent, Religious, Honest, Superior). Abstrak. Penggunaan hukuman sering digunakan oleh sekolah sebagai bentuk mendisiplinkan siswa mereka. Meskipun untuk mendisiplinkan anak tidak selalu harus menggunakan hukuman, melalui kesepakatan yang dibuat antara dua pihak dapat melatih disiplin dan tanggung jawab terhadap anak. Metode penelitian dilakukan dengan menggunakan metode kualitatif. Tujuan penelitian ini adalah untuk memberikan wawasan tentang perencanaan, proses, evaluasi dan hasil, serta faktor penghambat dan pendukung program disiplin positif. Pengumpulan data yang digunakan adalah wawancara, observasi, dan studi dokumentasi. Analisis data terdiri dari reduksi data, tampilan data, dan kesimpulan. Hasil penelitian menunjukkan bahwa (a) Merencanakan program disiplin positif di SMPN 15 Bandung dalam membentuk karakter siswa kelas VIII MAJU (Mandiri, Beragama, Jujur, Unggul).(b) Proses pelaksanaan program disiplin positif dalam membentuk karakter MAJU (Mandiri, Beragama, Jujur, Unggul). (c) Evaluasi dan hasil penerapan disiplin positif dalam membentuk karakter siswa kelas VIII MAJU (Mandiri, Beragama, Jujur, Unggul). (d) Faktor penghambat dan pendukung penerapan disiplin positif di SMPN 15 Bandung dalam membentuk karakter siswa kelas VIII MAJU (Mandiri, Religius, Jujur, Unggul).